Advanced Evapotranspiration Methods and Applications - Bucur, Daniel (IntechOpen, 2019)
Since the beginning of its formation approximately three billion years ago, the hydrosphere - as an envelope of the terrestrial ellipsoid - has remained constant from a quantitative point of view. The hydrosphere modifies only the ratio of the stretches of the planetary ocean and land, including the proportion of the states of water aggregation: gaseous, liquid, and solid.The hydrological cycle transports only a portion of the hydrosphere, repeats itself annually, and presents itself as a huge planetary plant that for billions of years has operated uninterruptedly on the basis of solar energy and gravity, providing freshwater resources for the maintenance and perpetuation of life beyond the planetary ocean.Water resources are highly influenced by the hydrologic cycle and play a role in agricultural economic development. However, as is shown by the Intergovernmental Panel on Climate Change report, the phenomena of changing climate and land use are set to exacerbate an already serious situation of water supply for various users. In this context, scientific investigations into the issue of the sustainable use of water are timely and important. Improvement of water management involves the accurate estimation of consumptive uses. The purpose of this book is to show the achievements of scientists and academicians all over the world in promoting and sharing new issues on various topics related to evapotranspiration.